Evaluating the effects of UPoCA prior to implementation: taking stock of where we were - Rusike, Joseph; Lukombo, S.S.; Msemo, J.; Osei-Sarfoh, A.; Fannah, S.; Okechukwu, R.U.; Jumbo, S.; Chibeba, A.M. (International Society for Tropical Root Crops, 2012)
Most development researchers and practitioners agree that the sharp rise in international prices for agricultural commodities that emerged in 2003 and peaked in 2008 resulted in a global food crisis. To combat the crisis, IITA and national partners in seven African countries are evaluating the effects of cassava research for development approach on increasing the productivity of production and processing of cassava for home consumption and marketing surplus produce. This paper uses farm household and econometric modeling with baseline and counterfactual data to predict the impact of implementing the project prior to its full implementation. The results show that cassava is at different stages of transformation from a famine reserve, food security crop and rural food staple to a cash crop for urban consumption and manufacture of industrial products. The impact of UPOCA will likely depend on the stage of transformation of the cassava sector in the country. UPoCA will likely have the most impact if interventions are aligned with the stage reached by the country.